Detection of Spirocerca lupi and an unknown Trichinella-like nematode in raccoon (Procyon lotor) - Torsten Langner; Domenico Otranto; Marcos Antonio Bezerra-Santos; Jan Franzen; Annette Johne; Daniele Tonanzi; Martin Pfeffer; Stefan Birka (International Journal for Parasitology: Parasites and Wildlife, 2024)
The raccoon Procyon lotor (Carnivora: Procyonidae) is an invasive species of growing importance for the introduction of alien pathogens or as additional hosts for autochthonous pathogens in Europe, including zoonotic parasites. As the population is steadily increasing and outcompeting the red fox (Vulpes vulpes) in Germany, the consumption of raccoon meat raises concerns about pathogens they may transmit. Therefore the presence of Trichinella larvae was here investigated in muscle samples (n = 904) of raccoons from northern Germany. No Trichinella larvae were found, thus confirming the general low occurrence of this parasite in Germany. However, Spirocerca lupi (n = 12) and an unidentified Trichinella-like nematode (n = 1) were accidently detected in the examined samples. The first is not a zoonotic parasite but has a high veterinary relevance as it can cause severe diseases in dogs. It is the first documented autochthonous infection of this nematode in Germany. The larvae of an unidentified Trichinella-like nematode were found in high abundance in all examined muscles of one raccoon, though they could not be identified to species level. Histological investigation revealed intramuscular cystic structures. This is the largest study investigating muscular parasites of raccoons in Europe so far, which suggests that this invasive animal species is infected by S. lupi and by a yet unknown Trichinella -like parasite.